1987
DOI: 10.1029/gl014i001p00076
|View full text |Cite
|
Sign up to set email alerts
|

Forced release of sodium from upper atmospheric dust particles

Abstract: The almost explosive growth of narrow sodium layers at altitudes near 95 km was observed by ground‐based LIDAR located at 69°N, 16°E. Starting from typical conditions at these altitudes (sodium density approximately 1 to 2× 10³ cm−3) the density is observed to increase by large factors within a few minutes in a narrow layer, the half height of which is typically 1 km only. One of the more spectacular cases involved an increase by a factor 25 within 5 min and a layer width of 0.8 km (full width at half maximum)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(44 citation statements)
references
References 15 publications
4
40
0
Order By: Relevance
“…Thus, Nas has been observed between low latitudes and high latitudes. In the high latitude observations, a strong correlations between Nas and sporadic E (Es) in the ionosphere occurrence has been observed and it is suggested that a neutral sodium atom is made from sodium ion (von Zahn et al 1987;von Zahn and Hansen 1988). It is noteworthy that the correlation between Nas and Es, based on the observations at Hachioji at mid-latitude was also reported (Nagasawa and Abo 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Nas has been observed between low latitudes and high latitudes. In the high latitude observations, a strong correlations between Nas and sporadic E (Es) in the ionosphere occurrence has been observed and it is suggested that a neutral sodium atom is made from sodium ion (von Zahn et al 1987;von Zahn and Hansen 1988). It is noteworthy that the correlation between Nas and Es, based on the observations at Hachioji at mid-latitude was also reported (Nagasawa and Abo 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Many Nas events were observed in the 1980s in Norway (69 N) (von Zahn et al 1987;von Zahn and Hansen 1988), and Longyearbyen, Svalbard (78 N) (Gardner et al 1988), Tokyo (35 N) (Nagasawa et al 1995), Mauna Kea, Hawaii (20 N) and Arecibo, Puerto Rico (18 N) (Beatty et al 1989). Thus, Nas has been observed between low latitudes and high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…There are several previous studies on this issue [von Zahn et al, 1987;Nomura et al, 1987;Gu et al, 1995;Heinselman et al, 1998;Heinselman, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…The occurring altitude of Na s layers is generally higher than the peak of the main layer and normally falls with time (Clemesha, 1995). The decay period of Na s layers is normally longer than their formation period (Kwon et al, 1988;von Zahn et al, 1987). In addition, simultaneous and common volume lidar observations at 30 • N showed that, 62 % of sporadic Na and Fe (Fe s ) layers occurred in overlapping altitude ranges and moved following almost the same track (Yi et al, 2007).…”
Section: Introductionmentioning
confidence: 96%